O ensino filosófico de Filosofia no contexto da escola em tempo integral como experiência possibilitadora da autonomia - ALMADA, José Antonio Souza (2021)
The present research has as its theme the teaching of philosophy in the context of full-time school. Its objective is to develop a methodology for philosophical teaching of philosophy from the Nietzschean perspective of education based on the idea of autonomy for life, which is constituted from the affirmative attitude that results from the eternal return of difference and that allows the student, for through the practice of self-care, becoming who he is. Its importance is in the fact that it corroborates for the achievement of the goal of the school full time, which is to train autonomous, solidary and competent young people. For this, it is assumed that, if philosophy classes are taught in such a way that the passive learning student of the content transmitted by the teacher, they can serve the student as a source of the necessary autonomy so that he can elaborate and execute the project. their life project autonomously, and thus take responsibility for its existence, becoming the protagonist of it. To test this hypothesis, a qualitative research was carried out using the “action research” method carried out with bibliographic, documentary, descriptive procedures and practical interventions. Despite the situation of social exclusion due to the Covid-19 pandemic and the context of teaching performed remotely in an improvised way, the research achieved the desired objective, which was evidenced by the competence that the participants demonstrated during the interventions, a competence that can be verified by the abilities that the students had to critically analyze the proposed themes, to problematize, to investigate and to position themselves autonomously on the themes. Therefore, it is concluded that yes, the philosophical teaching of philosophy can serve the student as an enabling element for the development of autonomy for life.